2019
DOI: 10.1016/j.ebiom.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

O-glycans truncation modulates gastric cancer cell signaling and transcription leading to a more aggressive phenotype

Abstract: BackgroundChanges in glycosylation are known to play critical roles during gastric carcinogenesis. Expression of truncated O-glycans, such as the Sialyl-Tn (STn) antigen, is a common feature shared by many cancers and is associated with cancer aggressiveness and poor-prognosis.MethodsGlycoengineered cell lines were used to evaluate the impact of truncated O-glycans in cancer cell biology using in vitro functional assays, transcriptomic analysis and in vivo models. Tumor patients ‘samples and datasets were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 69 publications
6
71
0
Order By: Relevance
“…Cell surface expression evaluation by FACS analysis revealed that the SC model displays an homogenous profile of Tn-/STn-expressing cells, whereas the ST6 model showed an heterogenous profile ( Figure 1C). This finding is in agreement with the fact that the ST6 model allows for partial O-glycan extension ( Figure 1A) [26,28,29]. In addition, further characterization of STn-expression dependency on cell cycle progression was analyzed.…”
Section: Glycoengineered Gastric Cancer Cell Lines Enable In Vitro Stsupporting
confidence: 88%
“…Cell surface expression evaluation by FACS analysis revealed that the SC model displays an homogenous profile of Tn-/STn-expressing cells, whereas the ST6 model showed an heterogenous profile ( Figure 1C). This finding is in agreement with the fact that the ST6 model allows for partial O-glycan extension ( Figure 1A) [26,28,29]. In addition, further characterization of STn-expression dependency on cell cycle progression was analyzed.…”
Section: Glycoengineered Gastric Cancer Cell Lines Enable In Vitro Stsupporting
confidence: 88%
“…Previous reports demonstrated that specific glycosylation signatures were detected in EVs, including large and small exosomes, relative to plasma membrane or microsomal glycoproteins [63,64], as well as in the recently described exomere subpopulation [5]. The cellular synthesis of STn has been shown to promote an aggressive malignant phenotype and is often associated with poor prognosis of gastric cancer patients [14]. Interestingly, the EVs derived from the gMKN45 were enriched on specific high molecular weight glycoproteins carrying the STn antigen, when compared with the whole gMKN45 cellular lysate.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour cells express a wide variety of glycosylation alterations, which interfere with key cancer cell processes and with the tumour microenvironment, contributing to cancer progression and patients' poor prognosis [8]. Particularly, the cancer‐associated glycan sialyl‐Tn (STn) has been shown to be highly related with tumour cell aggressive features, cancer metastasis and patients' poor survival [9–14]. This truncated structure results from a deregulation of the O ‐glycosylation biosynthetic pathway, such as overexpression of ST6GalNAc1 enzyme [15,16] or loss of function of Cosmc chaperone [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, MKN-45, MKN-74 and N87 cells presented significant oversialylation (e.g., m/z 933.5, 1178.7, 1294.7). MKN-45 exhibited more extended fucosylated and/or sialylated glycans, while MKN-74 were significantly enriched for the sialyl-T antigen and N87 cells presented shorter mono-and di-sialylated core 1 and core 2 glycans and the sialyl-Tn (STn antigen; m/z 729.4), a glycan known to play a critical role in GC invasion and metastasis [46,47]. Despite marked differences, MKN-45, KATO-III, OCUM-1 and N87 also exhibited a low abundance of ions (<5% relative abundance; m/z 1556.8, 1801.9 and 1917.9), potentially corresponding to glycans with terminal SLe epitopes, in accordance with flow cytometry analysis.…”
Section: Glycomics and Affinity For E-selectinmentioning
confidence: 99%